Vulnerabilidade da gravidez de alto risco na percepção de gestantes e familiares - Viviane Cazetta de Lima Vieira; Mayckel da Silva Barreto; Verônica Francisqueti Marquete; Rebeca Rosa de Souza; Mayara Maria Johann Batista Fischer; Sonia Silva Marcon (Universidade Federal do Ceará, 2019)
Objective to describe the perception of pregnant women and their relatives about the vulnerability of a high-risk pregnancy.Methods qualitative research with eight pregnant women and ten relatives. Data were collected through semi-structured, audio-taped interviews, which, after transcription, were submitted to content analysis in the thematic modality proposed by Bardin.Results three categories emerged: Experiences of relatives and pregnant women in relation to the diagnosis of a risky pregnancy; The family as the structuring axis of care in a high-risk pregnancy; and Invisibility of relatives in prenatal care.Conclusion both the relatives and the pregnant women experienced worry, anxiety, fear and stress in the face of vulnerability, but the pregnant women perceived themselves to be more protected and safer with the support of the family, which although did not perceived to be valued by health professionals during prenatal consultations, plays an important role in encouraging and supervising care during pregnancy.